(3ZGjI GdCeGfi aj CNHGQ GdbWQ GdjeGfis - (3jMji Hf GdMSjf Hf GdbGSe Hf eMeO, GHf GdbGpSe,J (B1099 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYRjR GdbgGQ s
(3GfXQg HQbe (B742 (3JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B192s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B173 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B192 s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydi CejQi (B(2375) s
Keywords: (3GdJGQjNs